2019
DOI: 10.1111/ans.15362
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of unplanned readmission to hospital post‐appendectomy: an opportunity for a new benchmark

Abstract: Background Appendicitis is the most common cause of acute abdominal pain requiring surgical intervention. While many studies report readmission, a meta‐analysis of readmission post‐appendectomy has not been published. This meta‐analysis was undertaken to determine rates and predictors of hospital readmission following appendectomy and to potentially provide a metric benchmark. Methods An ethically approved PROSPERO‐registered (ID CRD42017069040) meta‐analysis following Preferred Reporting Items for Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 74 publications
1
8
1
Order By: Relevance
“…In our series, about 20% of people required a longer hospital stay, consistent with other published studies 17,18 . Our study's reported indicators of complicated appendicitis, such as conversion to open surgery, hospital readmission and mortality rates are also consistent 4,19–21 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our series, about 20% of people required a longer hospital stay, consistent with other published studies 17,18 . Our study's reported indicators of complicated appendicitis, such as conversion to open surgery, hospital readmission and mortality rates are also consistent 4,19–21 …”
Section: Discussionsupporting
confidence: 91%
“…17,18 Our study's reported indicators of complicated appendicitis, such as conversion to open surgery, hospital readmission and mortality rates are also consistent . 4,[19][20][21] Indigenous patients tended to stay longer than their non-Indigenous counterparts. Very Remote patients (ARIA 5) had the longest LOS, median 2.6 days for Indigenous and 2.1 days for non-Indigenous patients.…”
Section: Discussionmentioning
confidence: 96%
“…Prior research has thoroughly investigated the 30-day readmission rates. CA affects the readmission with a lower rate in laparoscopic compared to open technique [ 33 , 34 ]. A recent meta-analysis substantiates that factors such as CA, diabetes mellitus, and open technique influence unexpected readmission within 30 days [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic appendectomy is associated with reduced 30-d readmission. In a meta-analysis including 45 studies and 836921 appendectomies, Bailey et al [ 103 ] has reported a 4.3% (range 0.0-14.4%) 30-d readmission rate. Diabetes mellitus, complicated appendicitis, and open appendectomy predicted 30-d readmission[ 103 ], and thus laparoscopic appendectomy may be superior if available and accessible.…”
Section: Management Of Appendicitismentioning
confidence: 99%
“…In a meta-analysis including 45 studies and 836921 appendectomies, Bailey et al [ 103 ] has reported a 4.3% (range 0.0-14.4%) 30-d readmission rate. Diabetes mellitus, complicated appendicitis, and open appendectomy predicted 30-d readmission[ 103 ], and thus laparoscopic appendectomy may be superior if available and accessible. Laparoscopic appendectomy is also notably more cost-effective compared to not only open surgery but NOM as well.…”
Section: Management Of Appendicitismentioning
confidence: 99%